Efektivitas Media Pembelajaran Berbasis Aplikasi Geogebra Dengan Pendekatan STEM (Science, Technology, Engineering, and Mathematics) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Andini, Risa Nur; Yuliardi, Ricki (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to explore and measure the effectiveness of using GeoGebra application-based STEM learning media in improving the mathematical problem solving ability of junior high school students. In this study, researchers took samples of two classes which will be divided into one control class and one experimental class. The class chosen as the control class is VII B and the experimental class is class VII E. With the experimental method, the two classes are divided into an experimental group (using GeoGebra) and a control group (conventional learning).  The research instruments used are in the form of description questions and questionnaires, while the data analysis techniques used are descriptive and inferential statistical analysis. This study used independent simple t-test, N-Gain test, and questionnaire processing. The results of the analysis showed that there was no significant difference in initial abilities between the two groups. However, after treatment, there was a significant increase in mathematical problem solving abilities in the experimental group. This is proven from the results of the post-test and N-Gain test. Student responses to the use of GeoGebra in learning mathematics with a STEM approach are also positive, showing high interest and understanding. These results support learning approaches that integrate technology and natural sciences, engineering, technology, and mathematics to improve students' mathematical problem solving skills